(untitled) (Bangladesh Journal of Microbiology, 2016)
Recently antibacterial activity of ten commonly available oral herbal medicines has tested in our laboratory. Current investigation further endeavoured to compute the microbial propagation in six more oral herbal medicines, including the drug resistance pattern of the microbial isolates, and antibacterial potential of the medicines by employing both agar well diffusion method and broth micro-dilution procedure to determine the minimum inhibitory concentration (MIC). Among the 30 samples of 6 categories studied, the total viable bacteria were found within the range of 104-107 cfu/ml, while the presence of fungi was noticed only in 3 samples up to 105 cfu/ml. All samples were found to be contaminated with Staphylococcus spp., 2 samples with Escherichia coli and 1 sample was found to be contaminated with Klebsiella spp. Most of the isolates showed resistance against commonly used 13 antibiotics; 80% isolates were found to be multidrug-resistant (MDR). All samples exhibited antibacterial activity with their MIC values up to 55 mg/ml. However, using the agar well diffusion assay, antibacterial activity was detected only in case of only 1 sample. Bangladesh J Microbiol, Volume 32, Number 1-2,June-Dec 2015, pp 15-19